Implementation of an Early Warning System Integrated with AIS-POLBENG Remote Base Station for the Safety of Traditional Ships in the Malacca Strait - Enda, Depandi; Supria, Supria; Romadhoni, Romadhoni; Hardiyanto, Hardiyanto; Faizi, M. Nur; Afridon, M. (Politeknik Negeri Bengkalis, 2024)
Referring to the Indonesian Minister of Transportation Regulation No. PM 7 of 2019 and IMO regulations onthe use of AIS devices, it is stated that AIS devices must be installed on passenger ships, cargo ships with a minimum sizeof 35GT, and fishing vessels of at least 60GT. However, smaller vessels under 60GT are also highly recommended to equipAIS devices to enhance maritime safety and security. This recommendation is based on several maritime accidentsinvolving traditional fishing vessels, which often lack safety equipment such as navigation tools and AIS devices.Therefore, the role of AIS devices is crucial for the safety of fishermen at sea, especially in preventing ship collisions,illegal fishing, and supporting SAR (Search and Rescue) operations. The high cost of AIS equipment presents a challengefor small-scale fishermen to afford these devices. This research aims to develop a more affordable alternative AIS devicebased on Lora technology, which offers similar functionality to standard AIS devices. The developed Lora Transpondercan also be integrated with the existing AIS-POLBENG system, thereby facilitating monitoring activities and providingearly warnings of potential hazards during sailing activities to traditional fishing vessels equipped with the device. Thesystem implementation results show that the Early Warning System operates as expected. The maximum coverage of AISTransponder data transmission is 49.87 Nautical Miles (92.36 Km). On the other hand, 3 units of lora transponder deviceshave successfully sent sensor and location data to the gateway every 30 seconds with the device set at class C andrecommended using binary format for more efficiency.